Konstantynopol w listach Teofilakta, arcybiskupa Ochrydy - Leszka, Mirosław J. (Vox Patrum, 2006)
The article discusses the manner adopted by Theophylakt, the archbishop of Ochrid, an eminent theologian, rhetor and teacher living at the end of the XIth and the beginning of the XIIth centuries, to describe Constantinople, the Capital of the Byzantine Empire.